PEMBUATAN BRIKET ARANG DAUN KELAPA SAWIT (Elaeis guineensis Jacq.) DENGAN PEREKAT PATI SAGU (Metroxylon sago Rott.) - Rahmadani, Rahmadani; Hamzah, Faizah; Hamzah, Farida Hanum (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Increasing need of energy and decreasing of fuel supply requires human to discover alternative energy resources. Consequently, there should be a research to discover a new renewable energy source such as palm leaves waste. Oil palm’s leaves (Elaeis guineensis Jacq.) are mostly the least used waste from oil palm plantation as an alternative energy resources. This research aims to discover the precise adhesive consentration rate in sago’s starch (Metroxylon sago Rott.) to make oil palm’s kernel, which are 97%:3%, 96%:4%, 95%:5%, 94%:6%, and 93%:7%. Based on analitycal result of oil palm’s leaves charcoal briquet research, the best quality briquet is the P1 composition which composed rate is 97%:3%, has 3,21% water content, 30,18% ashes content, 0,0022 g/s combustion rate, 20,73% evaporated substance rate, 54,46% carbon rate, and 5.114 cal/g heat value.  Keywords : briquet, oil palm’s leaves, sago starch adhesive.